A Cost-Effective Photonic Radar Under Adverse Weather Conditions for Autonomous Vehicles by Incorporating a Frequency-Modulated Direct Detection Scheme - Sharma, Abhishek; Chaudhary, Sushank; Malhotra, Jyoteesh; Saadi, Muhammad; Al Otaibi, Sattam; Nebhen, Jamel; Wuttisittikulkij, Lunchakorn (Frontiers in Physics, 2021)
Recent years have seen plenty of demands and growth of the autonomous vehicle industry and thus have encountered challenges of designing highly efficient photonic radars that can detect and range any target with the resolution of few centimeters. Existing radar technology is unable to meet such requirements due to limitations on available bandwidth. Another issue is to consider strong attenuation while working under diverse atmospheric conditions at higher frequencies. The proposed model of photonic radar is developed considering these requirements and challenges using the frequency-modulated direct detection technique. The result depicts improved range detection in terms of received power and acceptable signal-to-noise ratio and range under adverse climatic situations.